Meningkatkan Kreativitas Anak Usia Dini Melalui Metode Proyek di Paud KB Atirah Kabupaten Pangkaje dan Kepulauan - Nirwana Nirwana; Nasaruddin R; Mulyadi Mulyadi; Minarni Minarni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2022)
Abstract: Enhancing Early Childhood Creativity Through Proyek method in Paud KB Atirah Regency Pangkaje and Kepulauan. This research aims to increase early childhood creativity through the project method. In this study, thedata sum was group B of PAUD KB Atirah with 11 students. The object of researchis the creativity of children. Data collection techniques are carried out using observation, interviews and documentation. This research was carried out 2 cycles, each cycle lasted for 2 meetings. The results showed that children's creativity ability increased after PTK. The results of previous observationsshowed that children who had children's creative abilities through the project method had not met the criteria, in cycle I it increased to (33.5%.) and in cycle II it had reached success indicators (75%). Based on these results, it can be concluded that the project method can increase creativity in children in Paud KB Atirah, Pangkajene Regency and islands.